Field‐Effect Transistors: Tuning Frontier Orbital Energetics of Azaisoindigo‐Based Polymeric Semiconductors to Enhance the Charge‐Transport Properties (Adv. Electron. Mater. 11/2017). (22nd November 2017) - Huang, Jianyao; Chen, Zhihui; Mao, Zupan; Gao, Dong; Wei, Congyuan; Lin, Zuzhang; Li, Hao; Wang, Liping; Zhang, Weifeng; Yu, Gui
Abstract : In article number1700078, Gui Yu and co‐workers describe the design and synthesis of a class of donor–acceptor semiconducting polymers for use in field‐effect transistors (FETs). Multiple conformational controls within the polymer backbone, including S···N, Se···N, and C–H···N interactions, are realized to fine‐tune the molecular frontier orbital energies and backbone orientations. These polymers enable a deep understanding of the structure–property relationships involved in FETs and can change charge transport polarity from p‐type to ambipolar.